2016
DOI: 10.1080/21695717.2016.1197619
|View full text |Cite
|
Sign up to set email alerts
|

The written language of children with cochlear implant

Abstract: In the era of cochlear implants (CIs) and newborn hearing screening programmes, the oral language skills of deaf children have improved significantly. The literature documents sizable gains in their speech perception and receptive and expressive spoken language. However, the improvements in the area of reading and writing are less remarkable, and reading and writing continue today to be a major challenge for children with CIs. The article discusses the role of two cognitive factors that may contribute to make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The DHH group has repeatedly been reported to write fewer words, in the form of shorter texts compared to their monolingual and bilingual hearing peers. This is thought to be caused by a smaller vocabulary and a limited auditory input (e.g., Arfé et al 2016;Gärdenfors et al 2019;Oliveira et al 2020).…”
Section: Written Productmentioning
confidence: 99%
“…The DHH group has repeatedly been reported to write fewer words, in the form of shorter texts compared to their monolingual and bilingual hearing peers. This is thought to be caused by a smaller vocabulary and a limited auditory input (e.g., Arfé et al 2016;Gärdenfors et al 2019;Oliveira et al 2020).…”
Section: Written Productmentioning
confidence: 99%
“…The analysis of written text productions clearly shows a worse trend in the use of many linguistic aspects of written language by deaf participants, not only in the use of morphosyntactic rules but also in the ineffective use of an informative lexicon. Texts written by deaf participants were shorter than those produced by hearing controls (for comparable results on Italian subjects see Arfé et al, 2016; see also Daigle et al, 2020); they included a less informative lexicon, consistent with other studies focusing on the content and the communicative function of written texts (Gormley & Sarachan-Deilly, 1987;Wolbers et al, 2015). Overall, the description of skills in the performance of deaf subjects relative to the control group showed the following: reduced informational content, reduced length and richness of text, a poorer global impression of text content, lowered adherence to deliveries, impaired structure of the text, and a reduced level of correctness in both morphosyntax and punctuation.…”
Section: Discussionmentioning
confidence: 89%
“…In Italian subjects, several studies (e.g., Caselli et al, 2006;Chesi, 2006) reported peculiar features: the written productions of individuals with hearing impairment were characterized by a poor vocabulary and the formulation of short and telegraphic sentences with a simpler syntactic structure in comparison with productions by those without a hearing impairment. Overall, data indicate that texts produced by deaf people contain generally fewer words, being shorter than those composed by hearing peers, reportedly due to their limited language or literacy knowledge (e.g., Arfé et al, 2016;Gärdenfors et al, 2019;Oliveira et al, 2020). To explore this hypothesis, research has examined the effect of practice on syntactic competence of sentences written by deaf individuals.…”
Section: Introductionmentioning
confidence: 97%
“…First, deaf children lag behind their hearing peers in language development even with a CI or bilateral CIs [ 75 , 76 ], and even when they have been implanted at a very early age [ 77 ]. Delays are evident in their vocabulary, reading, and writing abilities [ 75 , 78 , 79 , 80 , 81 , 82 ]. Children with CIs exhibit weaknesses in complex, high-order language processing across the board [ 83 ].…”
Section: Risks Facing Deaf Childrenmentioning
confidence: 99%